REVOLUTIONIZING REAL-TIME BIG DATA PIPELINES WITH AI: A COMPREHENSIVE GUIDE - Rajkumar Sukumar (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This comprehensive article explores the transformation of real-time big data pipelines through artificial intelligence integration, addressing the evolving challenges in modern data processing environments. As organizations face increasing demands for real-time analytics and data processing, traditional pipeline architectures struggle to maintain efficiency and reliability at scale. The article examines how AI-driven solutions revolutionize key aspects of data pipeline management, including dynamic data ingestion, quality control, stream processing optimization, and resource management. Through analysis of implementation cases and industry research, it demonstrates how AI-enhanced pipelines improve data processing capabilities, reduce operational overhead, and enable more efficient resource utilization. The article particularly focuses on the role of edge computing, automated machine learning, and distributed systems in advancing pipeline performance. Additionally, it provides insights into implementation considerations, best practices, and emerging trends in AI-driven data pipeline management, offering organizations a framework for the successful adoption of these technologies in their data infrastructure.